As estratégias multimodais no gênero exposição oral - Galdino, Jebson da Silva (2020)
Orality is recognized as a linguistic modality of human expression in various contexts of social interaction. It allows man to share his thoughts and emotions about themes belonging to a given culture or society. Studies in the field of Linguistics and Education, as Marcuschi (2001) and PCN (1998), are in line in terms of identifying the precision of guiding the child to reflect on the function and practice of oral through oral genres. at school, as well as inserting it in literacy activities and real situations of oral productions. Today, with the notion of oral genres, the role of the school space in the development of oral skills is clearer, but, often, the school does not realize the relevance of orality in the teaching-learning process. This work, which is based on the interactional conception of language, aims to investigate the multimodal linguistic strategies that children use in the oral exposure genre in school space. Theoretically we rely on interactionist studies, among which we highlight: Bakhtin (1997), (2004), Marcuschi (2001) (2003) (2008) (2010), McNeill (1985), Schneuwly and Dolz (2004). Methodologically, the research falls within the descriptive and qualitative scope. Films of oral exhibition productions were taken by two children from the 2nd year of the literacy cycle of a school located in the city of João Pessoa. The data were transcribed and stored in the database of the Speech and Writing Acquisition Laboratory of (UFPB). The analyzes show the use of speech and multimodal elements such as: gesture, intonation, clapping, facial expressions, among others, in an integrated way in the entry and production of the oral exposure genre by children in the process of interaction with their audience. All of this becomes possible and more effective through the teaching of orality in the school space through oral genres. Thus, it is concluded that the gestures also "verbalize", composing a linguistic whole in a given social context of interaction. It is hoped that the contributions of this research can draw the school's attention to its role in the construction of oral skills in all their complexity in the literacy cycle.